Food in medieval England : diet and nutrition - Woolgar, C. M.; Waldron, T. (Tony); Serjeantson, D. (Dale) (Medieval history and archaeology., 2006)
This book draws on the latest research across different disciplines to present the most up-to-date picture of English diet from the early Saxon period up to c.1540. It draws on a wide range of sources, from the historical records of medieval farms, abbeys, and households both great and small, to animal bones, human remains, and plants from archaeological sites. - ;Food and diet are central to understanding daily life in the middle ages. In the last two decades, the potential for the study of diet in medieval England has changed markedly: historians have addressed sources in new ways; material.